2011
DOI: 10.1016/j.iref.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

International diversification and industry-related labor income risk

Abstract: Do equity markets help diversifying away industry-related labor income risk? This paper reconsiders the hedging role of stock markets by focusing on international equity diversi…cation, rather than domestic asset allocation, and on industry wage, rather than individual labor income. We test for di¤erences in implied equilibrium equity portfolios across investors belonging to di¤erent industry-country pairs. We compare these industry-based portfolio holdings to the one that is optimal for an investor endowed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…We point out that the estimate of the correlation coefficient over the whole sample yields a statistical zero value since individual correlations are widely scattered across negative and positive values. This argument supports and extends similar observations in Eiling (2013) and Fugazza, Gioifrè, and Nicodano (2011).…”
Section: Introductionsupporting
confidence: 93%
“…We point out that the estimate of the correlation coefficient over the whole sample yields a statistical zero value since individual correlations are widely scattered across negative and positive values. This argument supports and extends similar observations in Eiling (2013) and Fugazza, Gioifrè, and Nicodano (2011).…”
Section: Introductionsupporting
confidence: 93%
“…They show that introducing new financial assets, such as an equity portfolio that matches the industry composition of the persons in the cohort, leads to substantial welfare gains. Fugazza, Giofré, and Nicodano (2011) argue that the optimal portfolios of pension funds vary depending on the industry in which the members work.…”
mentioning
confidence: 99%
“…In addition, Kroencke and Schindler (2012) found that adding international real estate to an already internationally diversified equity portfolio resulted in a significant diversification benefit. It is evident that international diversification provides an important hedging opportunity in stock markets (Topaloglou et al 2002;Fugazza et al 2011). Nevertheless, U.S. investors still hold significantly less foreign stocks compared to the optimal number according to the portfolio theory (Herold and Maurer 2003).…”
Section: Optimal Portfolio Size Across Different Capital Marketsmentioning
confidence: 99%